Comparison of oral cavity protein abundance among caries-free and caries-affected individuals—a systematic review and meta-analysis - Silveira, Eliane Garcia da; Prato, Laura Schaurich; Pilati, Sarah Freygang Mendes; Arthur, Rodrigo Alex (Frontiers in Oral Health, 2023)
Some salivary proteins seem to be differently abundant among caries-free (CF) and caries-affected (CA) individuals, but previous results are contradictory precluding that definitive conclusion be drawn. A pooled analysis of the available evidence may provide more robust data on identifying oral cavity proteins patterns among CF and CA individuals. Objective: This systematic review and meta-analysis (PROSPERO CRD42021269079) aimed to compare the oral cavity´s protein abundance among caries-free and caries-affected individuals. Methods: This study was conducted following PRISMA guidelines. PubMed, Embase, and Web of Science databases were systematically assessed (up to Feb, 2023) to retrieve clinical studies written in English, German or in Latin-based languages that compared the oral cavity´s protein abundance among CF and CA individuals. Data extraction and methodological quality assessment (NIH guidelines) were independently performed by two investigators. Qualitative synthesis was performed from all included studies and meta-analysis was performed using a random effect model with inverse variance for studies that reported concentration of proteins or enzymatic activity. Standardized mean difference (SMD), with respective 95% confidence interval (CI) were calculated for each outcome. Results: 90 studies (2 cohort and 88 cross-sectional designs) of more than six thousand participants were selected for data extraction, being the quality of evidence graded as “fair” for most of them. The oral cavity of CF individuals presented lower total protein concentration (SMD=0.37 [CI 95%: 0.07; 0.68; 18 studies], lower total antioxidant capacity (SMD=1.29 [CI 95%: 0.74; 1.85]; 17 studies) and lower carbonic anhydrase activity (SMD= 0.83 [CI 95%: 0.58; 1.09]; 3 studies), whereas CA individuals presented lower carbonic anhydrase concentration (SMD=-0.66 [95% CI: -1.00; -0.32]; 3 studies) and lower urease (SMD= -0.95 [IC 95%: -1.72; -0.17]; 4 studies) and arginine deiminase system (SMD= -2.07 [IC 95%: -3.53; -0.62]; 3 studies) activities. Antimicrobial peptides and s-IgA concentrations and alpha-amylase activity was similar among individuals. Conclusion: Differences were observed on protein abundance among CF and CA individuals. These data indicate some proteins patterns for the oral health and for the dental caries conditions. Even when statistically significant, some of the results were not very consistent. Cohort studies need to be conducted to validate these results.